2018
DOI: 10.1007/s11046-018-0288-z
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Fungal Sinusitis Caused by Exserohilum rostratum and Literature Review

Abstract: A case of allergic fungal sinusitis (AFS) caused by Exserohilum rostratum, proven by culture and histopathology of the biopsy material, is described. The identity of the isolate was confirmed by sequencing of ITS region of rDNA. To the best of our knowledge, this is the first report of allergic E. rostratum sinusitis from Kuwait and Arabian Peninsula. Ten previously described cases of AFS have been reviewed. The report highlights the emerging importance of E. rostratum as a human pathogen in this region and ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The incidence of AFS is higher than in the international literature. The incidence of AFS is approximately 7% of all chronic sinusitis requiring surgery [13][14] . A literature review shows that the prevalence of AFS is higher in temperate regions with relatively high humidity.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of AFS is higher than in the international literature. The incidence of AFS is approximately 7% of all chronic sinusitis requiring surgery [13][14] . A literature review shows that the prevalence of AFS is higher in temperate regions with relatively high humidity.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids are given preoperatively and postoperatively to reduce inflammatory/allergic response which in turn helps to control peroperative bleeding and recurrence. 10,11 The goal of primary and revision surgery is the removal of mechanical obstruction, clearance of sinus contents and establishment of adequate outflow tracts while maintaining mucociliary function. 12 Identification of areas of bone erosion through recognition of defects, 12 in base of the skull and orbit is very important prior to surgery in order to prevent serious complications.…”
Section: Discussionmentioning
confidence: 99%
“…Bone erosion in AFRS results from fungal debris, secondary impacts of inflammatory mediators, and expansion of walls of paranasal sinuses, all of which cause pressure atrophy (Tsetsos et al, 2021). Numerous studies have reported bone erosion to radiographic and clinical findings in some patients of AFRS (Alajmi et al, 2019;Alharbi et al, 2023). However, limited literature on CT features of AFRS associated bone erosion exists.…”
Section: Introductionmentioning
confidence: 99%